Curso de inglês para fins de negócios (IFN) online baseado em tarefas orais no AVA Edmodo: um estudo de caso - Onodera, Jorge (2020)
This research is inserted in the Linguistic Studies area, specifically in the area of teaching-learning of foreign languages. The general objectives were: to apply and evaluate the effectiveness of a Business English (BE) course based on oral tasks, in distance learning, using active methodology and Digital Information and Communication Technologies (DICT); and to conduct a survey to identify the perceptions of LEA students course about their learning and about the BE course in distance learning using TDIC. To conduct this study I created an Business English Online (BEO) course based on oral tasks on the virtual learning environment Edmodo. The course is theoretically based on Duddley-Evans and St John (1998); Basturkmen (2010); Paltridge and Starfield (2013) regarding to ESP; Duddley-Evans and St John (1998), Ellis and Johnson (1994) regarding to Business English; in Moran (2015, 2016), Valente, Almeida and Geraldini (2017), Moran and Bacich (2018), with regard to the Active Methodology; Ribeiro (2008), Barrett e Moore (2011), Ansarian e Lin (2018) e Moran (2018) regarding Problem Based Learnig; in Almeida (2003), Anderson (2008), Moller and Huett (2012) for Distance Learning and on Ellis (2003), regarding Tasks. From a methodological point of view, it is a qualitative interpretative case study based on Stake (1995), Merrian (1998) and Yin (2005), developed in Edmodo and taught on online distance modality. The target audience was undergraduate students among the 1st and 4th semesters from a course entitled Foreign Languages Applied to International Negotiations (LEA) from two public universities in Brazil, one located in Ilhéus city, south of Bahia state, and the other one, from a federal center of technological studies located in Rio de Janeiro city. I carried out the data collection through questionnaires, interviews, audio and video recorded tasks and reflective reports on the course and tasks. Data were categorized based on the result of each task and the information provided by the students about their perceptions regarding the course and their learning. The survey results indicated that the Busines English Online course based on oral tasks developed for the research was efficient. The final product of tasks performance demonstrated that students were able to perform them efficiently, reaching a satisfactory result. The course was taught entirely in English, in the distance modality, using DICT to perform tasks with students from BA and RJ. The requirement to use DICT in the course provided students the opportunity to learn how to deal with the technologies available in work environments. The data showed that students' perceptions regarding their learning were positive. Students assumed their role in relation to their own learning. According to students' view, the course material contributed to good task performance in a proactive and successful way. The result on students' perception on the course demonstrated they had a favorable perception, praising the material provided, the dynamics of the course and the use of DICT to perform the tasks.